PENERAPAN AKAD AL-IJARAH PADA PERBANKAN SYARIAH SERTA KEUNGGULANNYA DIBANDINGKAN DENGAN BUNGA - Suhendra, Syam (LPPM STAI Muhammadiyah Probolinggo, 2025)
The interest system is considered the same as usury has triggered the creativity of Muslim scholars and economists to make contracts that are already known or not yet known as an instrument to replace interest, one of which is the al-ijarah contract (rental). The purpose of this paper is to determine the application of the al-ijarah contract in Islamic Banking and the advantages of al-ijarah compared to interest. The author conducted the research using the normative legal approach method. Furthermore, the data collection technique was by means of documentation study. Drawing conclusions using the qualitative normative analysis method. In the discussion, it can be seen that in Islamic Banking, the application of the ¬al-ijarah contract consists of: 1) Ijarah Mutlaqah where throughout the ijarah agreement period, ownership of the goods remains with the bank, at the end of the ijarah period, the bank can lease it back to another party or sell the goods; 2) Al-Ijarah al-Muntahia bit-Tamlik is a kind of combination between a sale and purchase contract and a lease or more precisely a lease agreement that ends with the ownership of the goods in the hands of the lessee, at the end of the agreement period, ownership of the goods is transferred to the lessee if the customer uses his option to buy the goods, but if the customer does not use his option then ownership of the goods remains with the bank. According to Islamic law, rent payments do not conflict with Islamic economic ethics because of the difference between rent and interest, rent does not contain elements of unfair treatment from creditors to debtors as occurs in interest.